Intonation and gestures in the interrogatives of the telenovela: Destino prohibido (Islas, 2022)
ABSTRACTIntroduction: In this work the analysis of the intonation patterns of the questions is carried out, in interaction with the gestures, in a sample of ten chapters of the Cuban telenovela Destino Prohibido. Total questions and partial questions are taken into account in all appearance contexts.Methods: A communicative approach is used and a perceptual analysis is carried out from the auditory and visual point of view that allows defining the intonation units and the elements related to gestures. The analysis ofintoneme patterns is based in the theory of Raquel García Riverón and the analysis of gestures in McNell´s classification.Results: The gesture, like the intonation peak, is used to draw attention to a certain part of the interrogative where want to emphasize, mostly, in relation to the lexical-grammatical structure.Conclutions: This study is part of a bigger project about expressiveness and affectivity in the intonation of the Cuban variety of Spanish in multimodal discourse. Until now, various uses of gestures that are integrated in correspondence with intonation patterns have been identified